TEACHING READING COMPREHENSION FOR GETTING THE FACTS BY USING GUIDED QUESTION TECHNIQUE - (F12207010), Emika; ., Sudarsono; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Penelitian ini terkait pada pemahaman reading comprehension siswa dalam teks narasi. Penelitian ini meneliti keefektifan dari guided question teknik untuk mengajarkan reading comprehension dari teks narasi untuk kelas 8 SMP Negeri 3 Kendawangan Tahun Akademik 2012/2013. Penelitian ini merupakan pre-eksperimental dengan siswa kelas VIII D sebagai sampel. Kelas tersebut terdiri dari 30 siswa. Alat pengumpulan data adalah tes tertulis yang berbentuk pilihan ganda. Data tersebut dianalisis dengan rumus effect size (ES). Hasil dari penelitian ini menunjukkan bahwa effect size (ES) adalahh 1,37. Angka efektifitas ini dikategorikan tinggi. Kata Kunci: Reading comprehension, narrative text, guided question technique Abstract: This research concerned the students reading comprehension of narrative texts. The research studied the effect size (ES) of guided question technique to teach reading comprehension of narrative texts to year-8 students of SMP Negeri 3 Kendawangan in Academic Year 2012/2013. It was a pre-experimental research with students of VIII D class as the cluster sample. The class consisted of 30 students. The tool of data collecting was a written test. It was a multiple choice test. The data were analyzed by effect size (ES) formula. The finding shows that the effect size (ES) was 1.37. it is categorized high effectiveness. Key words: Reading comprehension, narrative text, guided question technique